Improving the Community's Socio-Economic Quality Through Counseling on the Prevention of Early Marriage (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Adolescence is when education, experience, and the search for identity in the social environment. However, it is different in Parungponteng Village, Parungponteng District. Many social and legal cases have befallen its citizens, namely the rise of underage marriages. The age limit for marriage has been regulated by law. However, citizens' right to form a family and continue offspring through legal marriage, as stated in the 1945 Constitution, is to disseminate an understanding of the laws and regulations that govern it. Pre-test and post-test were also conducted to determine the level of understanding of the community. The results of counseling show that the understanding of early marriage is increasing. The results of the pre-test evaluation averaged 48.60 m after the post-test reached 69.56. Teenagers do early marriage with an age range of 15 to 17 years; some as young as 13 have married due to social, economic, and environmental factors. After knowing and understanding, the people of Parungponteng Village will be able to comply with the rules and improve the social and economic life of the community through land use activities that can contribute to meeting the necessities of life so that early marriages can be prevented.